Hey Y’all!

I decided to finally stand up a full site. Hosting on AWS and all that stuff. I am going to start writing on several different subjects.

Until Then Remember!

$$\ H(X) = -\sum p(X)\log p(X)\\Information\ Gain\; I(X,Y)= H(X)-H(X|Y)$$

Skip to content
# Category: Random_Thoughts

Hey Y’all!

I decided to finally stand up a full site. Hosting on AWS and all that stuff. I am going to start writing on several different subjects.

Until Then Remember!

$$\ H(X) = -\sum p(X)\log p(X)\\Information\ Gain\; I(X,Y)= H(X)-H(X|Y)$$